The Collaborative Portfolio: Exploring Reading Skills Through Peer Tutoring - Díaz Araque, Javier Enrique; Durán Blanco, Carlos Ernesto (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Our research emerges as an alternative to adopt the use of portfolios in EFLLicenciatura programs. As tutors in a peertutoring university project, we exploredtutees´ English reading skills as they used a collaborative portfolio with us, their tutors,during their free time. As a result of this research, we determined that the portfolioemerged as a “planner for tutees’ reading skills”, allowing themto establish objectivesfor boosting their comprehensive skills. Furthermore, the portfolio became an“enhancer of collaborative roles” between tutees and tutors. Finally, the portfolioallowed tutees to explore their own reading skills by supplying them with readingexperiences.